Assessing interpretive use of language in English translations of Al-Fatiha - Anandika Panca Nugraha (UPT P2M Politeknik Negeri Malang, 2016)
This article investigates the interpretive use of language in English translations of Al Fatiha taken from The Koran Interpreted by Arthur Arberry and The Qur’an: a New Translation by Abdel Haleem. This descriptive qualitative study uses Gutt’s relevance approach in assessing the choices made for interpretively communicating Al Fatiha’s message. The finding shows that Haleem’s translation is more interpretive with more fashionable and familiar structures and words requiring lower processing efforts. The choices imply that Arberry’s version is a scholarly translation while Haleem’s work is for popular use. Translating sacred texts should also consider translator’s cultural background and contextual knowledge.